Assessment of the strength and sorption properties of Nigerian made wood plastic composites (2012)
The strength and sorption properties of Nigerian made wood plastic composites used as building components were assessed. Results obtained indicated that the composites generally had low strength values and were dimensionally stable. The wood plastic composites can only be used for non-structural purposes in both interior snd exterior applications